1994
DOI: 10.1557/jmr.1994.3210
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure and morphology of carbon black: A study using small angle neutron scattering and contrast variation

Abstract: This is a study of the form and structure of particles and particle aggregates of an experimental high surface area carbon black (HSA) using small-angle neutron scattering and the method of contrast variation. Contrast variation was effected by studying suspensions of the carbon black in cyclohexane containing different fractions of deuterocyclohexane. We find that the approximately 29 nm diameter USA particles are arranged as small, linear aggregates with an average aggregation number between 4 and 6. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…The figure shows that the graphitization heat treatment shifts f(x) to considerably higher size values and due to this heat treatment the size distribution function becomes very narrow. The increase of the grain size of carbon blacks due to graphitization has been observed before by Raman, TEM, AFM, and also by X-ray diffraction using the Scherrer method [9][10][11]. These techniques proved that at elevated temperatures crystallites grow both in the lateral and vertical directions.…”
Section: Average Size Size Distribution and Shape Of Crystallitessupporting
confidence: 53%
See 1 more Smart Citation
“…The figure shows that the graphitization heat treatment shifts f(x) to considerably higher size values and due to this heat treatment the size distribution function becomes very narrow. The increase of the grain size of carbon blacks due to graphitization has been observed before by Raman, TEM, AFM, and also by X-ray diffraction using the Scherrer method [9][10][11]. These techniques proved that at elevated temperatures crystallites grow both in the lateral and vertical directions.…”
Section: Average Size Size Distribution and Shape Of Crystallitessupporting
confidence: 53%
“…Energies of adsorption of different adsorption sites and their relative populations have recently been evaluated by gas adsorption technique [8]. The sizes of graphitic crystallites have been estimated from X-ray diffraction [5,9], neutron scattering [10], Atomic Force Microscopy [11], and Raman spectroscopy measurements [3][4][5]. Those studies showed that the average size of crystallites, L a , is similar for all commercial carbon black grades produced in furnace reactors and roughly equal 2.3 nm.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, D1 is systematically varied with the introduction of a deuterated fluid or the isotopic substitution of deuterium for hydrogen in one of the components. Deuterium has a very different scattering length than hydrogen, so by varying the amount of deuterium present, different structural features can be emphasized (or deemphasized) [8,10,16].…”
Section: Usans Analysismentioning
confidence: 99%
“…Liu et al [4] compared the failure behaviour of nano-SiO 2 fillers epoxy coating under hydrostatic pressure with that under atmospheric pressure, the results indicated that high hydrostatic pressure accelerated the failure of organic coating by promoting diffusion of water in the coating. They also [5] considered that both physical and chemical properties between inorganic fillers and organic binder contribute to a bad interfacial compatibility [13]. Our previous studies indicated that a large number of defects on the coating surface such as pores were generated by the addition of inorganic fillers [4][5][6].…”
Section: Introductionmentioning
confidence: 99%